Transcriptomic Analysis in Strawberry Fruits Reveals Active Auxin Biosynthesis and Signaling in the Ripe Receptacle - Estrada-Johnson, Elizabeth; Csukasi, Fabiana; Pizarro, Carmen M.; Vallarino, José G.; Kiryakova, Yulia; Vioque, Amalia; Brumos, Javier; Medina-Escobar, Nieves; Botella, Miguel A.; Alonso, José M.; Fernie, Alisdair R.; Sánchez-Sevilla, José F.; et al. (Frontiers in Plant Science, 2017)
The role of auxin in ripening strawberry (Fragaria ananassa) fruits has been restricted to the early stages of development where the growth of the receptacle is dependent on the delivery of auxin from the achenes. At later stages, during enlargement of the receptacle, other hormones have been demonstrated to participate to different degrees, from the general involvement of gibberellins and abscisic acid to the more specific of ethylene. Here we report the involvement of auxin at the late stages of receptacle ripening. The auxin content of the receptacle remains constant during ripening. Analysis of the transcriptome of ripening strawberry fruit revealed the changing expression pattern of the genes of auxin synthesis, perception, signalling and transport along with achene and receptacle development from the green to red stage. Specific members of the corresponding gene families show active transcription in the ripe receptacle. For the synthesis of auxin, two genes encoding tryptophan aminotransferases, FaTAA1 and FaTAR2, were expressed in the red receptacle, with FaTAR2 expression peaking at this stage. Transient silencing of this gene in ripening receptacle was accompanied by a diminished responsiveness to auxin. The auxin activity in the ripening receptacle is supported by the DR5-directed expression of a GUS reporter gene in the ripening receptacle of DR5-GUS transgenic strawberry plants. Clustering by co-expression of members of the FaAux/IAA and FaARF families identified five members whose transcriptional activity was increased with the onset of receptacle ripening. Among these, FaAux/IAA11 and FaARF6a appeared, by their expression level and fold-change, as the most likely candidates for their involvement in the auxin activity in the ripening receptacle. The association of the corresponding ARF6 gene in Arabidopsis to cell elongation constitutes a suggestive hypothesis for FaARF6a involvement in the same cellular process in the growing and ripening receptacle.